Influencia de Canavalia ensiformis l. en tres poaceas forrajera en el rendimiento de la biomasa aérea en Zungarococha – 2022 - Moris Perez, Ricardo Gamaniel (2022)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Cattle Project in the Zungarococha Farm, entitled INFLUENCE OF Canavalia ensiformis L. IN THREE FORAGE POACEAS ON THE YIELD OF AERIAL BIOMASS IN ZUNGAROCOCHA - 2022”. The evaluations were carried out 60 years after the beginning of the research work, with vegetative seed (bushes), in plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 141.1 m2. With a Randomized Complete Block Design (D.B.C.A), with four treatments and four repetitions, the treatments under study were: T0 (Without Association), T1 (Association of canavalia + Green King grass), T2 (Association of canavalia + King grass purple), T3 (Association of canavalia + Maralfalfa), obtaining the following results: A yield of plant height of 1.72 m., A yield of green matter (kg/m2) and dry matter (kg/m2) of 3.94 kg/ m2 and 0.87 kg/m2 respectively, in percentage of plant coverage (%) of 94.75%. in Leaf/stem ratio (Kg) of 0.62 kg with T3 (Association of canavalia + Maralfalfa) and green matter yield kilos/hectare of 39 375. In this sense, it was shown that the association of canavalia plus green King grass influenced in the area biomass yield significantly.